Application of Running Average Function to Non-Dispersive Errors of Network-Based Real-Time Kinematic Positioning - Lim, Samsung; Rizos, Chris; Musa, Tajul A (International Association of Chinese Professionals in Global Positioning Systems (CPGPS), 2008)
The GPS errors can be separated into a frequency-dependent or dispersive component (e.g. the ionospheric delay) and a non-dispersive component (e.g. the tropospheric delay and orbit biases). Dispersive and non-dispersive errors have different dynamic effects on the GPS network corrections. The former exhibits rapid changes with high variations due to the effect of free electrons in the ionosphere, whilst the latter change slowly and smoothly over time due to the characteristic behaviour of the tropospheric delay and the nature of orbit biases. It is found that the non-dispersive correction can be used to obtain better ionosphere-free measurements, and therefore helpful in resolving the long-range integer ambiguity of the GPS carrier-phase measurements. A running average is proposed in this paper to provide a stable network correction for the non-dispersive term. Once the integer ambiguities have been resolved, both dispersive and non-dispersive corrections can be applied to the fixed carrier-phase measurements for positioning step so as to improve the accuracy of the estimated coordinates. Instantaneous positioning i.e. single-epoch positioning, has been tested for two regional networks: SydNET, Sydney, and SIMRSN, Singapore. The test results have shown that the proposed strategy performs well in generating the network corrections, fixing ambiguities and computing a user’s position.